Factor Analysis of Antenatal Care in Women of Fertilizing Age in Nepal - Resham Khumar Gautam; Manu Pallikadavath; Kishowed Rahman; Muhammad Aleem Shahid Khan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The high maternal and infant mortality rate in Nepal is a global problem. Antenatal Care (ANC) services are an effort to reduce maternal and infant mortality rates. This study aims to analyze factors in the utilization of antenatal care among women of childbearing age in Nepal. This research method The Nepal Demographic and Health Survey (NDHS) was carried out in the new era with official approval from the Ministry of Health and Population (MoHP), and the data collection period lasted from January 5 to June 22, 2022. The study population was women aged 15 to 49 years. who have given birth or experienced a stillbirth in the previous two years and have attended at least one antenatal care (ANC) visit. Data collection using questionnaires interviewed after they were discharged from the facility that provides delivery services. Data analysis using the JASP version 18 application to see the influence of the independent variable on the dependent variable. Bivariate data will be analyzed using chi-square analysis, and multivariate data will be analyzed using the logistic regression test. The research results showed that there was a relationship between age (p<0.001), place of residence (p<0.001), zone of residence (p<0.001), economy (p<0.001), education (p<0.001), number of children (p<0.001) women of childbearing age in Nepal with ANC visits. These factors greatly influence women of childbearing age in utilizing ANC services. Therefore, it is necessary to strengthen ANC service policies and remind women of childbearing age to make at least 4 ANC visits during pregnancy so that examinations and visits for pregnant women can be carried out completely. Keywords : Antenatal Care, Women of childbearing age, Nepal